THE EFFECT OF HOTS INSTRUCTION ON THE CRITICAL THINKING SKILLS OF FIFTH-GRADE STUDENTS AT NURUL QOMAR ELEMENTARY SCHOOL IN THE CIVIC EDUCATION COURSE - Siti Azzuhra Fadhillah; Sahkholid Nasution (SOSIOEDUKASI, 2026)
This study aims to determine the effect of Higher Order Thinking Skills (HOTS)-based learning on the critical thinking ability of fifth-grade students in Civic Education (PPKn) at SD Nurul Qomar. The study employed a quantitative approach using a quasi-experimental design with a one group pretest-posttest model. The participants consisted of 25 students selected through a saturated sampling technique. Data were collected through tests, observations, and documentation, and analyzed using descriptive statistics, the Shapiro-Wilk normality test, and the Paired Sample T-Test with SPSS. The results showed an increase in the average score from 65.40 in the pretest to 78.76 in the posttest. The normality test indicated that the data were normally distributed. The hypothesis test showed a significance value of less than 0.05, indicating a difference between scores before and after treatment. HOTS-based learning encouraged students to be more active in analyzing problems, expressing ideas, and drawing logical conclusions.